Polymorphisms of Il-10 (-1082) and RANKL (-438) Genes and the Failure of Dental Implants. (28th February 2017) - Ribeiro, Rodrigo; Melo, Rayanne; Tortamano Neto, Pedro; Vajgel, André; Souza, Paulo Roberto Eleutério; Cimões, Renata
Abstract : Background . Genetic polymorphisms in certain cytokines and chemokines have been investigated to understand why some individuals display implant flaws despite having few risk factors at the time of implant. Purpose . To investigate the association of genetic polymorphisms in interleukin- (IL-) 10 [-1082 region (A/G)] and RANKL [-438 region (A/G)] with the failure of dental implants. Materials and Methods . This study included 90 partially edentulous male and female patients who were rehabilitated with a total of 245 Straumann dental implants. An implant was considered a failure if any of the following occurred: mobility, persistent subjective complaint, recurrent peri-implant infection with suppuration, continuous radiolucency around the implant, probing depth ≥ 5 mm, and bleeding on probing. Buccal mucosal cells were collected for analysis of RANKL438 and IL-10 . Results . The implant success rate in this population was 34.4%. The mutant allele (G) in RANKL had an incidence of 52.3% and mutant allele (A) in IL-10 was observed in 37.8%. No statistically significant difference was detected between the failure of the implant and the genotypes and allelic frequencies. Conclusion . No association was detected between the genetic polymorphisms of RANKL (-438) and IL-10 (-1082) and the failure of dental implants in the population studied.